Persamaan, Perbedaan, dan Pola Penggunaan Satuan Lingual yang Mengandung Pronomina Persona Ketiga Pada Teks Terjemahan Alquran dan Teks Terjemahan Hadis Riwayat Buchori-Muslim - Faizah, Naimul, Prof. Dr. Markhamah, M.Hum, Prof. Dr. Abdul Ngalim, M.M.,M.Hum (2017)
The purpose of this study, there are three. (1) Identify the equation use lingual unit that contains personal pronouns third on TTA and TTH. (2) Identify the different uses lingual unit that contains third-person pronouns in TTA and TTH. (3) Identify the usage patterns lingual unit that contains third-person pronouns in TTA and TTH. This study includes the qualitative research. Subjects in this study is the translated text of the Koran and the Hadith containing the translated text speak ethics. The object of this research is the third personal pronouns in the text translation of the Koran and the Hadith containing the translated text speak ethics. The data in this study of the clause containing the unit lingual pronominal third person on TTA and TTH containing ethics speak. Data collection techniques in this study using methods refer to. In addition, use the same documentation techniques. The data analysis was conducted using a unified and agih methods. The results of the study there was 3. (1) Found similarity lingual unit from the category (noun, noun phrases, prepositional phrases, and phrase attributive); function (subject, predicate, object, complement, rules of origin, description of the place, tooltip, attributes of the subject, object attributes, and a tooltip), and roles (actors, patient, recipient, origin, presence, experiencer, tools, goals, known , participants, attributive, and designation). (2) Found differences with regard to categories (verb phrase and phrases numeralia), function (the time information, the offender, the offender, the designation, participation, cause, manner, exceptions, results, and presence), and roles (action, objective, identification, time, cause, exceptions, results, circumstances, and how the TTA. Roles are explained and the TTH). (3) In connection with the findings of the pattern changes lingual unit that contains third-person pronouns in TTA and TTH found patterns of change in the noun into a verb phrase, noun into a prepositional phrase, noun into a noun phrase and attributive nouns into phrases. Pattern function No 17 (subject, predicate, object, complement, description of the place, time, tools, origin, actors, designation, purpose, participation, cause, manner, exceptions, results, and presence. The pattern of the role, there are 22 (the role of actors, action, directions, receiver, presence, patient, objective, identifiers, known, identification, designation, tools, time, experiencer, attributive, cause, origin, exceptions, results, circumstances, participation, and how.